2016
DOI: 10.1089/cap.2015.0151
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Change in Corrected QT Interval in Children and Adolescents Receiving Antipsychotic Treatment: A 12 Month Study

Abstract: In this sample, SGA seem to have a safe heart side effect profile in the child and adolescent population. There was no observed mean increase in QTc or in heart rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Concerning ECG evaluation, our study showed that the treatment with aripiprazole and risperidone was related with a mostly unmodified mean QTc. This study underlines the relative cardiac safety of aripiprazole and risperidone in children and adolescents, even after 1 year of therapy, as reported in previous investigations (41,42). However, two of the enrolled patients treated with risperidone had a QTc exceeding 450 ms that led to the discontinuation of therapy before 12 months.…”
Section: Monitoring Of Parameters Over Timesupporting
confidence: 77%
“…Concerning ECG evaluation, our study showed that the treatment with aripiprazole and risperidone was related with a mostly unmodified mean QTc. This study underlines the relative cardiac safety of aripiprazole and risperidone in children and adolescents, even after 1 year of therapy, as reported in previous investigations (41,42). However, two of the enrolled patients treated with risperidone had a QTc exceeding 450 ms that led to the discontinuation of therapy before 12 months.…”
Section: Monitoring Of Parameters Over Timesupporting
confidence: 77%
“…Our findings are also consistent with the meta-analysis done by Jensen et al (2015) that also showed no statistically significant change in QTc with risperidone-treated children compared to placebo. Alda et al (2016) evaluated the effects of atypical antipsychotics (risperidone, olanzapine, or quetiapine) on QTc in an open-label study of 211 youth with various psychiatric disorders treated for 3-12 months. Of the 118 risperidone-treated subjects with ECG data at baseline, complete 1-year data were available on 34 subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical research assessing the effect of antipsychotics on QTc prolongation in youth (children and adolescents) have recently been performed in response to the increasing use of these drugs in this age group and have produced mounting evidence for a low risk of drug-induced QTc prolongation associated with antipsychotics use in this age group (Correll et al . 2011; Alda et al . 2016; Palanca-Maresca et al .…”
Section: Introductionmentioning
confidence: 99%